Investigation on a longitudinal discharge ultra-violet gas laser - Ng, Kok Foo Albert; Kwek, Kuan Hiang; Low, Kum Sang (Penerbit Universiti Sains Malaysia, 2004)
Longitudinal discharge refers to a method of electrically discharging an elongated confined geometry, in which the discharge current moves coaxially with the axis of the elongation geometry. Longitudinal discharge has always been employed to obtain visible and infra-red laser emission in the early days of laser research. Laser light is emitted coaxially with the discharge current through the tube end opening.